Gastrectomy and subsequent risk of oesophageal cancer in Milan. Issue 3 (June 1994) - La Vecchia, C; D'Avanzo, B; Negri, E; Franceschi, S; Boyle, P
Abstract : STUDY OBJECTIVE--To analyse quantitatively the relationship between gastrectomy and oesophageal cancer risk. DESIGN--This was a case-control study, based on a structured questionnaire that included a problem-oriented medical history. SETTING--A network of hospitals in the Greater Milan area between 1984 and 1992. SUBJECTS--Subjects were 316 incident, histologically confirmed cases of oesophageal cancer (258 males and 58 females), and 1408 controls (1031 males, 377 females), admitted to hospital for acute, non-neoplastic, non-digestive tract conditions. MEASUREMENTS AND MAIN RESULTS--Relative risks (RR) and the corresponding 95% confidence intervals (CI) adjusted for age and sex, plus area of residence, education, tobacco, and alcohol consumption. There was an association of borderline significance of oesophageal cancer with gastric ulcer (RR = 1.6), but not with duodenal ulcer (RR = 0.9). Among cases, 25 (7.9%) reported a history of gastrectomy, versus 29 (2.1%) of the controls. The corresponding multivariate RR was 3.8 (95% CI 2.0, 7.0). The RR of oesophageal cancer was significantly raised (RR = 3.6) within 20 years after gastrectomy, and the association seemed stronger with increasing time since gastrectomy (RR = 4.2). CONCLUSIONS--Since gastrectomy may cause gastric hypoacidity and favour oesophageal reflux, and hence oesophagitis, the results of this study, if confirmed, are of interest to a better understanding of the mechanisms of oesophageal carcinogenesis.